CuCo2S4 Deposited on TiO2: Controlling the pH Value Boosts Photocatalytic Hydrogen Evolution. Issue 38 (6th August 2020) - Poschmann, Michael; Groß, Hendrik; Amin, Reza; Fritsch, Charlotte; Dankwort, Torben; Radinger, Hannes; Indris, Sylvio; Kienle, Lorenz; Bensch, Wolfgang
Abstract : Metallic spinel‐type CuCo2 S4 nanoparticles were deposited on nanocrystalline TiO2 (P25®), forming heterostructure nanocomposites. The nanocomposites were characterized in detail by X‐ray powder diffraction (XRD), high‐resolution transmission electron microscopy (HRTEM), nitrogen sorption (BET) and UV/Vis spectroscopy. Variation of the CuCo2 S4 :TiO2 ratio to an optimum value generated a catalyst which shows a very high photocatalytic H2 production rate at neutral pH of 32.3 µmol/h (0.72 mL h –1 ), which is much larger than for pure TiO2 (traces of H2 ). The catalyst exhibits an extraordinary long‐term stability and after 70 h irradiation time about 2 mmol H2 were generated. An increased light absorption and an efficient charge separation for the sample with the optimal CuCo2 S4 :TiO2 ratio is most probably responsible for the high catalytic activity. Abstract : Nanosized metallic CuCo2 S4 deposited on TiO2 shows high photocatalytic hydrogen evolution using triethanolamine as sacrificial agent. Controlling the pH value boosts the photocatalytically produced amount of hydrogen. An enormous long‐term stability of the composite is obtained at neutral pH value.